In their own voices: factors effecting collegiate hockey player use and perception of mental skills - Burbidge, E. (The Sport Journal, 2025)
Mental skills use and perceptions of their effectiveness in collegiate level athletes have been studied extensively in sport psychology. The usage of mental skills has been deemed effective overall and in collegiate settings. That said, little research has investigated hockey players` perceptions of mental performance. Due in part to the unique culture of hockey there is a need to study hockey players` perceptions of, and influences on the use of, mental skills. Therefore, this study aimed to investigate the perceptions and usage of mental skills in collegiate hockey players, along with perceptions of how hockey culture impacts these beliefs through interviews with current college hockey players. Semi-structured interviews of six collegiate hockey players took place. Findings from these interviews suggest that level of play, exposure, and hockey culture largely impact how participants use and perceive mental training. These findings also suggest that some collegiate hockey players may be using psychological strategies without having been deliberately taught these strategies.